2015
DOI: 10.1063/1.4935509
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Dynamical and structural analyses of solid hydrogen under vapor pressure

Abstract: Nuclear quantum effects play a dominant role in determining the phase diagram of H2. With a recently developed quantum molecular dynamics simulation method, we examine dynamical and structural characters of solid H2 under vapor pressure, demonstrating the difference from liquid and high-pressure solid H2. While stable hexagonal close-packed lattice structures are reproduced with reasonable lattice phonon frequencies, the most stable adjacent configuration exhibits a zigzag structure, in contrast with the T-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…This comes from the qualitative structural difference; the supercooled liquid has the rigid T-shape structure in the first solvation shell, while the solid maintains the zigzag lattice configuration to realize the long-range stable lattice. 25 We note that integration up to the minimum at 4.8Å of the supercooled liquid gave a lower value than the solid peak integration reflecting its lower density. The first peak at 3.1Å less intense than the second peak at 3.8Å also indicates freer orientational motions in the supercooled liquid and thus its liquidity even at 2.5 K. As shown in Fig.S1 † , however, the main peak position and its width did not shift nor change at 2.5 K through 13 K due to stiffness of the first solvation shell of the supercooled liquid; only the relative intensity of the first peak over the second peak decreased with increasing the temperature reflecting freer orientational motions at the higher temperature.…”
Section: Basic Properties Of Supercooled Hydrogen Liquidsmentioning
confidence: 62%
See 2 more Smart Citations
“…This comes from the qualitative structural difference; the supercooled liquid has the rigid T-shape structure in the first solvation shell, while the solid maintains the zigzag lattice configuration to realize the long-range stable lattice. 25 We note that integration up to the minimum at 4.8Å of the supercooled liquid gave a lower value than the solid peak integration reflecting its lower density. The first peak at 3.1Å less intense than the second peak at 3.8Å also indicates freer orientational motions in the supercooled liquid and thus its liquidity even at 2.5 K. As shown in Fig.S1 † , however, the main peak position and its width did not shift nor change at 2.5 K through 13 K due to stiffness of the first solvation shell of the supercooled liquid; only the relative intensity of the first peak over the second peak decreased with increasing the temperature reflecting freer orientational motions at the higher temperature.…”
Section: Basic Properties Of Supercooled Hydrogen Liquidsmentioning
confidence: 62%
“…Density of the supercooled hydrogen liquid was set by extrapolating the saturated vapor-pressure line toward the lower temperature region 27 ; e.g. the molar volume is 24.2 × 10 −6 m 3 /mol at 2.5 K, 24.4 × 10 −6 m 3 /mol at 5 K, 25.1 × 10 −6 m 3 /mol at 10 K, 25.5 × 10 −6 m 3 /mol at 12 K, and 25.8 × 10 −6 m 3 /mol at 13 K which are all larger than the solid molar volume 25 . We started cooling and equilibration runs from the h.c.p.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous publications [32,33], we demonstrated that a model of floating and breathing localized electron wave * E-mail: ando_k@lab.twcu.ac.jp packets (EWP) with non-orthogonal valence-bond (VB) spincoupling [34][35][36][37][38][39][40] can be used to construct potential energy surfaces for single electron motion (ePES) as functions of the EWP positions. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain an alternative perspective, we have been studying a model of localized electron wave packets (EWPs) with non-orthogonal valence-bond (VB) spin-coupling [31][32][33][34]. It was originally developed for a polarizable and reactive forcefield model in condensed phase simulations to be combined with nuclear wave packets for light atoms [35][36][37][38]. For small molecules such as H 2 , LiH, BeH 2 , CH 2 , H 2 O, and NH 3 in * E-mail: ando k@lab.twcu.ac.jp the ground electronic state, the model gives reasonably accurate potential energy surfaces with the minimal number of EWPs [32].…”
Section: Introductionmentioning
confidence: 99%